Maternal and Perinatal Risk Stratification in Cardiovascular Pathology. A Modern View on the Problem - Siromakha, S. O.; Davydova, Yu. V.; Limanska, A. Yu.; Lazoryshynets, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Objective: to increase the safety of a patients with cardiovascular pathology during the implementation of their reproductive function, by presenting a modern strategy of medical support for such women based on the assessment of the maternal and perinatal risks. Cardiac pathology is the leading cause of morbidity in pregnant women and an indirect cause of maternal mortality. In recent decades, the focus on the problem of safety of pregnant women with the pathology has been steadily increasing. Stratification of patients by cardiovascular risk (CVR) consists of assessing the functional capacity of the patient, cardiac medications needs, history of previous cardiac events, diagnosis of structural, anatomical, and physiological changes and parameters of heart remodeling, and, if necessary, genetic counseling. An important point is to inform the patient about the potential risks and make a consensus decision with her about the possibility of safe implementation of her reproductive function. The authors of the paper analyze the CVR assessment scales used in leading medical practices and the national health care system as well, discuss current clinical guidelines for risk stratification and registered strategies for pregnancy and delivery management depending on the class of CVR in such patients. This paper presents the basic principles of medical support for women of reproductive age with pathology of the heart and great vessels in the form of an algorithm developed by the National pregnancy heart team. Determination of the degree of risk allows to prepare a woman with cardiovascular pathology for the pregnancy and delivery (medical correction or preventive cardiac surgery). Research on the identification and categorization of maternal and perinatal CVR factors and stratification of pregnant women by risk classes are extremely relevant and continue in the framework of the international study ROPAC (Registry Of Pregnancy And Cardiac disease). Ukrainian multidisciplinary team (on the base of two academic State Institutions – “National Amosov Institute of Cardiovascular Surgery” and “Institute of Pediatrics, Obstetrics and Gynecology named after acad. O.M. Lukianova”) takes an active part in this international collaboration.